A study on coordination training interventions by procedural memory and ideomotor performance among recreational athletes with coordination deficiency/disorder in Malaysia and Bangladesh - Ahmed, Maruf (2018)
Present study intended to compare the efficacy of electromyography (EMG)- assisted perceptual motor training (PMT), conventional coordination training (CCT) and combination of both interventions (CI) in improving the level of procedural memory and ideomotor performance in young-adult recreational athletes identified as having coordination deficiency (CD). This study was carried out in two different experimental set-ups and in two different countries. Forty young-adult participants (18-24 years) from Malaysia (N = 40) and eighty participants from Bangladesh (N = 80), were screened following identical selection criteria and were matched according to extent of CD. Participants in both set-ups were randomly categorized into four groups (one control and three experimental groups, with n = 10/group in Malaysia and n = 20/group in Bangladesh). Control group (Gr. I) participants did not receive any intervention, Group II participants received CCT; Group III received training of EMG-PMT and Group IV participants received CI. Thereafter pre-intervention analyses were carried out in both set-ups, based on bilateral & cross-lateral coordination; visual-motor conditioning; dexterity; simple and complex reaction time; cognitive parameters and muscle-potentiality indices as factors for procedural memory and ideomotor performance associated with coordinated performance. Thereafter participants of the experimental groups were introduced to their respective intervention training. Protocol for the interventions was scheduled as 15-20 minutes/day; 2 days/ week; for 16 weeks, followed by gradual and identical increment in difficulty level (15 minutes/session first two levels, 20 minutes/session for 3rd and 4th difficulty-levels). After 8 weeks of intervention, mid-term evaluation was carried out, and after 8 more weeks of intervention, post-intervention assessment was carried out at the end of 16th week. After 12 weeks of no intervention, post follow- up assessment was done to verify the extent of sustainability of the interventions. Two-way repeated measure of ANOVA revealed significant improvement in left and right lateral motor control, in clockwise and counterclockwise movements, in outcomes of EMG Average-Spectrum Zero-Crossing Rate index, in cognitive comprehension and working memory, which were evident among both Malaysian and Bangladeshi participants of experimental groups. For Malaysian participants, in case of both procedural memory and ideomotor performance, CCT emerged as the most effective intervention followed by the CI. For Bangladeshi participants, EMG-PMT was identified as most effective intervention in improving procedural memory followed by both CCT (for motor and movement coordination) as well as CI (for cognitive and EMG parameters) techniques. In case of ideomotor performance, EMG-PMT was identified as most effective intervention technique.